ADAPTIVE OPTICS : Possibilities of joint application of adaptive optics technique and nonlinear optical phase conjugation to compensate for turbulent distortions. (1st June 2016) - Lukin, V P; Kanev, F Yu; Kulagin, O V
Abstract: The efficiency of integrating the nonlinear optical technique based on forming a reverse wavefront and the conventional adaptive optics into a unified complex (for example, for adaptive focusing of quasi-cw laser radiation) is demonstrated. Nonlinear optical phase conjugation may provide more exact information about the phase fluctuations in the corrected wavefront in comparison with the adaptive optics methods. At the same time, the conventional methods of adaptive optics provide an efficient control of a laser beam projected onto a target for a rather long time.